A retórica bélica da IURD: um estudo sobre as postagens da Igreja Universal do Reino de Deus no twitter - Araujo, Emerson Ricardo (2022)
This paper analyzes the forms of interaction between the Igreja Universal do Reino de Deus – IURD on Twitter – through its official profile in Brazil – and its attenders and/ or followers, in order to identify the strategies used to communicate, the distinguishing marks of the discursive formation in which the church is inserted and seeks to identify the subject of speech in the IURD. For that, it uses the French Discourse Analysis (FDA) theory as support, in order to understand how the IURD’s discourse is inscribed in the Brazilian social context, especially in the Twitter virtual space, and since the issue of religiosity inserts itself in different discourses, referring to various social subjects of different discursive formations, we confront these discourses to, in this way, submit them to the DA proposal. The methodological path followed supports the analysis of posts of a militaristic nature, made in the official profile of the IURD on Twitter in the last two years, in order to observe how the language reveals the positions taken from the discourse used or even from the silencing of its enunciator.